Stabilitas Hasil Jagung Pulut Bersari Bebas pada Dataran Rendah Tropis - HG, M Yasin; Santoso, Sigit Budi; Faesal, Faesal; Talanca, A Haris; Mejaya, Made J (Jurnal Penelitian Pertanian Tanaman Pangan, 2017)
The young cob of waxy corn is consumed like sweet corn, however, waxy corn is glutinous and delicious because due to the low content of amylose which is less than 10.0%. The yield of waxy corn is commonly low around 2.0-3.0 t/ha and early maturity which is harvested in 85 days. Therefore, the yield has been improved through the intra population improvement S1 families selection. Nine genotypes were evaluated to select good population adapted under lowland condition in central corn production. The aims of reseach were to find of population (g) of maize waxy corn which good stability and average yieled was more than average in all locations. Randomized complete block design with four replications was conducted in five district (e) of central corn production (Maros, Polman, Manado, Probolinggo, Pakanbaru) on dry and wet season (s) under lowland in 2011. The spacing 75x20 cm, one plant per hill, genotypes was planted in 5.0 m lenght in four rows, and fertilized with Urea, SP36 and KCL (300-200-100) kg/ha. The yield stability was founded significant of interaction genotype x environment x season (g x e x s) and yield be increase if good environment also would increase (b>1.0) and average yield>total average in evt. The result showed that population PMS-D (Pulut Muneng Synthetics with grain texture of dent) be founded of yield 5.56 t/ha and 5.82 t/ha under wet and dry season or more than 17.0% than local check varieties (PH). Simple correlatin of yield PMS-D were significant on weight of seeds, ears weight, number of seeds in ear, and 1000 weight of seeds. There are not significant correlation of yield with amylase, carbo hydrate, protein and fat. The character’s of population was score one on plant aspect, husk cover, and ear aspect. The position of ear was middle of plant height, flowering in 45 days. The best population of PMS-D would be promising as new candidate of open pollinated variety and could increase farmers income than local waxy variety.